Amorphous Ni-P coating modified by laser remelting: The effect of remelted crystallization layer on microhardness and wear resistance. (December 2022) - Wu, Yucheng; Zhang, Zhaoyang; Xu, Kun; Dai, Xueren; Zhu, Hao; Ni, Tao; Liu, Yang
Abstract: Electrodeposited amorphous Ni-P alloys have enormous internal stress and high brittleness, resulting in cracks and poor wear resistance. In this study, the surface cracks of an amorphous Ni-P coating, prepared by laser-assisted electrodeposition were removed by laser remelting. The surface quality was characterized and the wear mechanism was analyzed by evaluating its microhardness and wear resistance. The results showed that the remelted layer had a corrugated structure, and the surface roughness increased. The remelted layer is transformed from amorphous to crystalline, consisting of stable phases of Ni, and Ni-P compounds. Compared with the non-remelted coating, the microhardness and wear resistance of remelted coating are improved. The main wear mechanisms of remelted coatings include abrasive wear, oxidation wear, and plastic deformation. Graphical Abstract: ga1